PROBLEMS OF GENERAL AND TYPOLOGICAL THEORY OF COMPOSITE SENTENCE WITH A PARENTHETICAL CLAUSE AS AN INVARIANT TYPE OF SYNTACTIC UNIT (to the statement of question of parenthetical introductory and insertive clauses) (Scientific journal of the Fergana State University, 2024)
The article touches upon the problem of the theory of invariant types of syntactic units, mainly of composite sentences which need a unified approach, for there are a huge number of notions and terms, one way or another relating to various aspects of the latter indiscriminately treated and commented on. In the article an attempt has been made by the author to take inventory of the existing invariant types of syntactic units, which are traditionally considered to be five-fold, but the author has revealed and established one more invariant type of composite sentence termed by him “a composite sentence with a parenthetical clause” of the two subtypes: a) introductory clause and b) insertive clause, realizing the new “introductory and insertive syntactic relations” termed by the authors accordingly: 1)introduction; 2) insertion like syntactic relations “coordination” and “subordination”, hence, as to the author, introductory and insertive clauses function, like other clauses, as introductory and insertive parts of matrix clause.